Sleep pattern and staging in elite adolescent rugby players during the in-season competitive phase compared to an age matched non-athlete population - Saidi, O.; Pereira, B.; Peyrel, P.; Maso, F.; Doré, E.; Rochette, E.; Ratel, S.; Walrand, S.; Duché, P. (European Journal of Sport Science, 2022)
Young athletes must contend with the constraints of elite sports on top of school commitments and the physiological processes associated with adolescence. This study assessed week and weekend sleep and schedule of activities in elite adolescent rugby players during the in-season competitive phase compared with age-matched non-athlete controls. 32 adolescents (GR: 16 elite rugby players, GC: 16 controls) from the same boarding school filled out a daily schedule of activities and a sleep diary, and wore a multichannel electroencephalogram for 14 days. They later filled out questionnaires on their sleep quality, sleepiness, and perceived stress. Both groups showed insufficient sleep duration during the week (<7 h). Only GC caught up on their sleep debt during the weekend (increased TIB, TST and time spent in REM sleep, all p < 0.001). Weekend TIB, TST and, N3 sleep remained similar to that for weekdays in GR. However, GR experienced lower sleep quality (decreased SE, increased WASO, all p < 0.01) and a decrease in REM sleep (p < 0.01). Schedules of activities showed an increase in time spent on overall activities during the weekend, mainly due to competition and sport-specific travel, which resulted in a decrease in sleep opportunity time compared with GC (p < 0.001). ? sleep opportunity time (weekend-week) was associated with Delza TST (weekend-week), and ? TST (weekend-week) was associated with sleepiness and perceived stress. Busy schedules during the competitive season decreased sleep opportunity time and prevented elite adolescent rugby players from catching up on their sleep at weekends.